(untitled) - Bennett, Dean B. (Washington, 2001)
In The Wilderness from Chamberlain Farm, historian Dean B. Bennett traces those transformations, bringing to life the people involved, their motivations, and the interconnected effects of their actions. Beginning 10,000 years ago with the retreat of the glaciers, Bennett offers an overview of the forces that shaped the land, and the visitors to and inhabitants of this place once known as Apmoojenegamook - "lake that is crossed
Keywords: Wilderness areas,Human ecology,Nature; History,History,Effect of human beings on,History; Maine,Chamberlain Farm,Maine,Chamberlain Farm,Maine,Chamberlain Farm